PENGARUH UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - Bambang Widjanarko Susilo; Heru Yulianto; Galuh Aditya (STIE Pelita Nusantara Semarang, 2022)
The purpose of this study is to analyze the effect of firm age and firm size on audit delay, as well as the mediating effect of profitability from firm age and firm size on audit delay. The research population is all companies listed on the LQ-45 Index on the Indonesia Stock Exchange in 2015-2019 as many as 44 companies so that the number of samples is 220 samples. The sampling technique used was purposive sampling method. After carrying out the normality and outlier test process, so that the data used in the study became 165 data. The data analysis technique used is path analysis and multiple regression. The results of this study indicate that the effect of negative firm age is not significant on profitability, while negative firm age has a significant effect on profitability. Firm age and firm size have a significant negative impact on audit delay. Negative profitability is not significant to audit delay. Profitability can be an intervening variable on the effect of firm age and firm size on audit delay.